A STUDY ON QUANTITY OF Bt TOXIN IN Bt AND NBt COTTON RHIZOSPHERE - Sujatha, T.; Raagini, P. Siva; Vijayalakshmi, K. (European Scientific Journal, ESJ, 2015)
Genetically engineered plants and their residues may pose direct or indirect impacts on different ecosystem functions. The aim of this experiment was to determine the amount of Bt toxin (Cry 1 Ac Î´ endotoxin) present in the rhizosphere of Bt cotton during the crop period at regular intervals. Bt toxin was estimated from the rhizospheric soils of near isogenic Non Bt cotton crop for as a control. Cry 1 Ac Î´ endotoxin was estimated using Envirologix Quanti Kit plate (ELISA) method. The soil samples were collected in which Bt cotton was cultivating for more than ten years as monocrop, similarly Non Bt cotton fields where never cultivated transgenic crop were selected for this study. The quantity of the Cry 1Ac toxin levels in the rhizosphere of Bt cotton was estimated at different crop stages and it was 41.13 ppb at pre cultivation stage which is higher than that of Non Bt rhizosphere soil i.e.15.3 ppb. The toxin concentration increased gradually during different crop stages i.e 69.32 ppb, 95.24 ppb, 103.35 ppb at 30, 60,90 days crop stages respectively. It was decreased to 92.37 ppb at harvest stage and shown higher levels (173.24 ppb) at postharvest stage. But in case of Non Bt rhizosphere it is almost same at all the stages of crop. The results suggests that there is a significant difference between the Bt and Non Bt soils with respect to quantity of Cry toxin and there is also significant difference between different crop stages of Bt cotton with respect to Non Bt cotton